MUTU STICK IKAN BELUT (Monopterus albus) DENGAN PENAMBAHAN TEPUNG KARAGENAN: The Quality of Eel (Monopterus albus) Fish Stick with Addition of Carrageenan Flour - Hidayah, Nur; Taher, Nurmeilita; Montolalu, Lita; Wonggo, Djuhria; Reo, Albert; Lohoo, Helen (Media Teknologi Hasil Perikanan, 2024)
Indonesia is endowed with a plethora of diverse animal food sources, one of which is the eel fish (Monopterus albus). Eel is a fish that can be consumed as a functional food, exhibiting a higher nutritional content than ordinary foodstuffs and providing health benefits for the body. Eel is processed into a variety of products, including the eel fish sticks. It is anticipated that the production of eel fish sticks with the incorporation of carrageenan flour will enhance the cohesiveness and binding power of the product, thereby extending its shelf life. The objective of this study was to assess the quality of eel fish sticks (Monopterus albus) with the incorporation of carrageenan flour through organoleptic evaluations, fat content analyses, crude fiber assessments, and water content examinations. The results of the study indicated that the panelists preferred the 0% carrageenan flour treatment in terms of organoleptic characteristics, including taste, color, texture, and aroma, when compared to treatments with 5%, 10%, and 15% carrageenan flour. The water content value was found to be lower with the addition of 5% carrageenan (6.78) compared to the addition of 0% carrageenan (7.52). The fat content value with a 5% carrageenan addition (9.71) was found to be lower than that observed with a 0% carrageenan addition (11.03). The crude fiber content exhibited a higher value with the addition of 5% carrageenan (0.78) compared to the 0% carrageenan addition (0.48). Similarly, the dietary fiber content demonstrated a higher value with the addition of 5% carrageenan (0.60) compared to the 0% carrageenan addition (0.44). Kata kunci:  Carageenan, Eel, Monopterus albus, Stick   Indonesia memiliki kekayaan sumber pakan hewani yang beragam, salah satunya ikan belut (Monopterus albus). Belut adalah ikan yang dapat dikonsumsi sebagai pangan fungsional yang memiliki kandungan nutrisi yang lebih tinggi dari pangan biasa dan dapat memberikan manfaat kesehatan bagi tubuh, belut tersebut diolah menjadi produk dengan cara diversifikasi. Sehingga dalam penelitian ini dilakakukan pembuatan stick ikan belut dengan penambahan tepung karagenan diharapkan dapat meningkatkan kekompakan dan daya ikat produk serta meningkatkan daya simpan pada stick ikan belut. Tujuan dari penelitian ini yaitu untuk mengetahui mutu stick ikan belut (Monopterus albus) dengan penambahan tepung karagenan melalui uji organoleptik uji kadar lemak, uji serat kasar, dan uji kadar air. Hasil Penelitian pada nilai organoleptik panellis lebih menyukai perlakuan tepung karagenan 0%, dari segi rasa, warna, tekstur, aroma, dibandingkan dengan penambahan karagenan sebanyak 5%, 10% dan 15%. Nilai kadar air dengan penambahan karagenan 5% (6,78) lebih rendah dibandingkan dengan penambahan karagenan 0% (7,52). Nilai kadar lemak dengan penambahan karegenan 5% (9,71) lebih rendah dibandingkan dengan penambahan karagenan 0% (11,03). Nilai kadar serat kasar dengan penambahan karegenan 5% (0,78) lebih tinggi dibandingkan dengan penambahan karagenan 0% (0,48). Nilai kadar serat pangan dengan penambahan karagenan 5% (0,60) lebih tinggi dibandingkan dengan penambahan karagenan 0% (0,44). Kata kunci:  Belut, Karagenan, Monopterus albu, Stick.